Clinical features of Sarcoidosis in Oman: A report from the Middle East region - Jayakrishnan, B; Al-Busaidi, Nasser; Al-Lawati, Ahsan; George, Jojy; Al-Rawas, Omar A; Al-Mahrouqi, Yaqoub; Al-Lawati, Nabil (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Though clinical features of sarcoidosis follow a similar pattern, some heterogeneity is seen in different ethnic and racial groups. Objectives: To describe for the first time the clinical characteristics of sarcoidosis patients in the Sultanate of Oman. Methods: The data on all cases of sarcoidosis followed up in the two tertiary hospitals in Oman were retrieved retrospectively. Results: Of the 92 patients, for representing the ethnic data only Omani patients (n=83) were included. The mean age was 52.90±12.35 years. Majority were females (72.3%, n=60). Cough (n=44, 53.0%), dyspnea (n=39, 47%), arthralgia (n=26, 31.3%) and fatigue (30.1%) were the major symptoms. Arthralgia was reported by 41.7% of the females and 4.3% of the males (p= 0.001). Uveitis was present in 16 (19.3%), erythema nodosum in 8 (9.6%) and hypercalcemia in 13 (15.7%). The radiological stage at presentation was stage 0, 18.7%; I, 28%; II, 17.3%; III, 24% and IV, 12%. Majority (61.4%) of the patients had tissue diagnosis; intra-thoracic site 70.6%. Pulmonary function showed abnormal diffusion in 75%. Sixty eight received treatment, 81.9% took prednisolone. Based on radiograph good outcome (Resolving) was noted in 20.9%, intermediate (Stable) in 73.1% and poor (Progressive) in 6%. Lung function wise, resolving, stable and progressive disease was seen in 31.4%, 40.0% and 28.6% respectively. Conclusion: The clinical picture of the patients with sarcoidosis from Oman was similar to that reported from the rest of the world. Region wise, our patients were older and arthralgia and hypercalcemia were more common. The management of sarcoidosis needs a more organized approach in the country with clear guidelines on monitoring and treatment